Effect of Draft and Season on Physiological Responses of Bullocks - Behera, B K; Mohapatra, A K; Behera, D; Swain, S (Journal of Agricultural Engineering, 2008)
The study on the physiological responses of medium sized Surungi (non-descript breed of Orissa) bullocks showed that the pulse rate (PR) increased sharply after one hour of work at all drafts in all seasons except at 10 % body weight draft. But sharp rise of respiration rate (RR) was observed in summer only. Thereafter, the rise of PR and RR were gradual. The PR and RR increased significantly with draft in summer and rainy season but not in winter season. Comparison of the PR and RR within seasons at a particular draft and duration showed that PR and RR were significantly higher in summer compared to rainy and winter season. The body temperature (BT) increased gradually with duration of work in summer and rainy season but not in winter season. However, sharp rise of BT was observed in winter after 151 hour of work. The interaction of draft and duration at a particular season was non significant, whereas within season there was significant variation in BT and was highest in summer at a particular draft and duration. The PR and RR recovered to its resting values after the rest during the noon except in case of respiration rate in summer at higher draft (14% of bodyweight). The body temperature did not recover to its resting values after the rest period in the noon in all seasons.